A Conceptual Framework for Leadership Development: Integrating Leader Identity, Personality Traits, and Learning Styles with Gen AI - Kasra Jaru Munara; Usep Suhud; Hamidah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Leadership development programs often adopt a one-size-fits-all approach, overlooking the individual needs of leaders based on their identity, personality traits, and learning styles. This paper develops a conceptual model for leadership development that integrates leader identity, personality traits, and learning styles within a differentiated training and adaptive learning framework. By leveraging Generative AI, the model personalizes training content to enhance engagement, effectiveness, and organizational impact. The paper identifies theoretical gaps in leadership development literature and proposes an innovative approach that bridges these gaps, contributing to both theory and practice. Future research is recommended to empirically validate the proposed model